An investigation of the geriatric nurses’ guideline-based practice of suctioning for elderly patients (老年病房护士践行吸痰操作规范现状的横断面调查) - ZHOU Xiaojuan (周晓娟); ZHAO Xin (赵鑫) (中西医结合护理)
Objective To investigate and analyze the geriatric nurses’ guideline-based practice of suctioning for elderly patients, and to provide reference for clinical nursing practice and management. Methods A cross-sectional survey was conducted and a total of 200 operations were observed with 76 nurses from geriatric wards. Furthermore, this study statistically analyzed the situations that did not match the guides and standards, and discussed the correlation between negative pressure range, duration, several basic information, and incidence of suction complications, the probability of suctioning all sputum at once. Results More than half of the nurses had three or more irregular behaviors during sputum suction operations. Before suctioning, 62. 00%(124/200) of nurses did not wash their hands, 61. 00%(122/200) of nurses failed to evaluate the signs, 23. 50%(47/200) of nurses had contaminated gloves and 36. 00%(72/200) of nurses did not check the negative pressure. The negative pressure value and duration of sputum suction used by nurses this time were greater than the values recommended in the guides. For every 1 mm Hg increase in negative sputum suction pressure, the probability of suctioning all sputum at once increased by 1. 90% (P＜0. 05). For every 1 second increase duration of intratracheal suctioning, the probability of suctioning all sputum at once increased by 3. 50% (P＜0. 05), while the incidence of related complications increased by 1. 90% (P＜0. 05). Conclusion There was a low consistent rate between nurses’ behavior and clinical guidelines. Nursing managers should improve quality issues in response to irregular nursing behavior, guide nurses to control the duration of an intratracheal sputum suction time and appropriately increase the negative pressure of phlegm suction in order to find the best suctioning effect. (目的 了解和分析老年病房护士在临床实际工作中践行吸痰护理实践指南及规范的现况, 为临床护理实践和管理提供参考。方法 采用横断面调查, 观察并记录某三甲医院76名老年病房护士的200次吸痰操作, 将其中与指南和规范不符的情况进行统计分析, 并探讨吸痰选取的负压范围、持续时长及几项基本信息与吸痰并发症发生率和一次吸净痰液率的相关性。结果 超过半数护士在吸痰操作中发生三种及以上的不规范行为, 62. 00%(124/200)的护士吸痰前未洗手, 61. 00%(122/200)的护士在吸痰前未评估吸痰指征, 23. 50%(47/200)的护士吸痰前手套污染, 36. 00%(72/200)的护士在吸痰前未检查负压, 本次护士所采取的吸痰负压值和吸痰持续时间均大于指南中推荐数值。此外, 吸痰负压每增加1 mm Hg, 一次吸净痰液的成功率就会提高1. 90%(P＜0. 05); 一次气管内吸痰时间每增加1 s, 一次吸净痰液率就会提高3. 50%(P＜0. 05), 同时相关并发症的发生率增加1. 90%(P＜0. 05)。结论 护士实施吸痰操作时存在较多与指南和规范不符的行为, 护理管理者需要针对不规范的护理行为进行质量问题改善, 同时指导护士控制一次气管内吸痰时间, 适当增大吸痰负压, 以寻求最佳吸痰效果。)